Jurisdiction clause included in the general terms and conditions. Purpose to the CJEU Judgement of 24th November 2022, case C-358/21 - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The TJ admits the suitability of a jurisdiction agreement between entrepreneurs when the clause is contained in standard terms accessible through a link sent by the predisposing party, provided that there is the possibility of accessing them before the conclusion of the contract, save and print them, and this even if it has not been necessary to check an acceptance box.
Keywords: Lugano Convention; Brexit; general terms and conditions; click-wrap agreements